Hubungan Inisiasi Menyusu Dini dan Rawat Gabung dengan Produksi Air Susu Ibu pada Postpartum di RSU Anutapura Palu - Pani, Widya (Poltekkes Kemenkes Palu, 2019)
Early Initiation of Breastfeeding can prevent infant mortality, especially in developing countries. IMD practices can prevent 22% of newborn mortality. One of the reasons mothers do not give IMD is the absence of breast milk and the amount of breast milk that is considered lacking, so the mother gives formula milk. Mothers don't take care of joining because they don't breathe spontaneously and hypothermia. The purpose of this study was to find out the relationship of early breastfeeding initiation and care to join with the production of breast milk at post partum at the Anutapura General Hospital in Palu. The method is analytic with a cross sectional approach. The population and samples in this study were post partum at Anutapura Palu Hospital at the time of the study, which amounted to 96 people, with a purposive sampling technique. The analysis used in this study used fisher exact statistical tests. The results showed that of 96 IMD respondents as many as 75 respondents (78.1%), and not IMD as many as 21 respondents (21.9). Mothers who did join care were 76 respondents (79.2%), and mothers who did not take care of as many as 20 respondents (20.8).